Assessment models in two project based learning (PBL) approaches: An exploratory study - Mesquita, Diana (2018)
Project Based Learning approach (PBL) has been a curricular and pedagogical asset in several engineering programs. According to the literature, PBL is based on a project being developed by teams of students in order to solve a problem connected with the profession, linking theory and practice. This learning context create opportunities for students to develop a set of technical and transversal competences related to engineering professional practice. In PBL there is no universal models, but a diversity of approaches. They are similar by the main principles of PBL, but different by the way they happen in practice. Implementing PBL implies rethinking the teaching and learning approach, in terms of contents, faculty collaboration, pedagogical spaces, and strategies for students’ support, amongst other. Particularly, assessment has been widely discussed in several studies. In order to contribute for an in-deep reflection about this topic, this paper aim to present two PBL assessment models in different contexts: a) PIEGI – Master Degree in Industrial Engineering and Management at University of Minho, Portugal; b) 100% PBL model in Engineering courses at UNISAL, Lorena, SP, Brazil. The assessment model in both contexts were analysed, based on documental analysis (pedagogical documents related to the projects). The information was organized and analysed in order to identify differences and similarities in both models. Implications of assessment in PBL and practical recommendation are presented in order to provide more inputs about this topic.